1987
DOI: 10.1099/00221287-133-9-2601
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Glycosyltransferase Production and Membrane Fatty Acid Composition of Streptococcus sanguis NCTC 7865 Grown in the Presence of Protonmotive Force Inhibitors

Abstract: The fatty acid composition of Streptococcus sanguis NCTC 7865 was not altered by changing the cation composition (Na+/K+) of the growth medium; glucosyltransferase (GTF; EC 2.4.1.5) also remained constant. In contrast, fructosyltransferase (FTF-S; EC 2.4.1.10) production was reduced by at least 50% in medium with a high Na+ concentration. Growth in the presence of ionophores (gramicidin, nigericin or valinomycin) resulted in an increased proportion of saturated fatty acids, principally octadecanoic acid (C18:0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

1989
1989
2000
2000

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…While we found that increasing the [Na+] of the tnedium did decrease GTF production by strain Challis in a similar manner to that reported by Keevil et al (18) for strain NCTC 7865, we found Tween 80 to be inhibitory to GTF production by strain Challis. Furthermore, in our experiments GTF secretion by strain NCTC 7865 was not stimulated by addition of Tween 80 to the growth medium as it was previously reported to be (35). The growth conditions and the method we used to assay GTF activity were both different to those used by West et al (35).…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…While we found that increasing the [Na+] of the tnedium did decrease GTF production by strain Challis in a similar manner to that reported by Keevil et al (18) for strain NCTC 7865, we found Tween 80 to be inhibitory to GTF production by strain Challis. Furthermore, in our experiments GTF secretion by strain NCTC 7865 was not stimulated by addition of Tween 80 to the growth medium as it was previously reported to be (35). The growth conditions and the method we used to assay GTF activity were both different to those used by West et al (35).…”
Section: Discussionmentioning
confidence: 70%
“…Secretion of the GTF enzyme by strain NCTC 7865 is influenced by the [Na + ]/[K+] ratio in the growth medium (18) and its secretion was shown previously to be stitnulated by Tween 80 (35). Tween 80 has also been shown to stimulate GTF production by S. mutans OMZ176 (34) and by S. salivarius ATCC 25975 (36).…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Adaptation is known to involve enhanced F 1 F 0 -ATPase (H -ATPase) activity [1,2,9,13], as well as enhanced production of an Exo-III-like, DNA-repair enzyme [8]. The responses of oral streptococci to a variety of environmental stresses such as temperature shifts [11,14], alcohols [16] or ionophores [22] involve changes in membrane fatty acid composition. This sort of response is very common among bacteria [5].…”
Section: Introductionmentioning
confidence: 99%